Use The Geographic Information Systems (GIS) In Protected Area Management (Naby Matta – Tartous) For Developing Eco-Tourism - Dayoub, Fadi; Abbas, Hikmat; Idriss, Younes (Latakia University Journal -Biological Sciences Series, 2013)
The eco-tourism is an important element in the economic and social development at the both local and international levels. It represent an essential economic resource for the governmental sector, so this research particularly important because it is looking for the possibility of using GIS techniques in the protected areas management. The objective of this study is to verify the GIS importance in creating data-base which is significant for Naby Matta protected area managers; this data-base is basically helping in the development of the ecotourism. The results of research confirmed the importance of geographic information systems in designing of database and the various maps and its role in determining the steps tourism development such as determining the places of assimilation and classify it according of the visitors density, select the better tracks for pedestrians, the appointment of entry points and restaurants, observation points, in addition to the investment potential of geographic information systems in spatial analysis such as proximity and distance analysis of particular point from another point, or search for a particular tourist attraction and find it such as searching for the best spots to enjoy the picturesque scenery away from sensitive environmental housing thus saving time and effort and speed in the service of visitors.